The renin angiotensin system and the brain: New developments. (December 2017) - Farag, Ehab; Sessler, Daniel I.; Ebrahim, Zeyd; Kurz, Andrea; Morgan, Joseph; Ahuja, Sanchit; Maheshwari, Kamal; John Doyle, D.
Highlight: Functions of the RAS on brain include neuroprotection, cognition and cerebral vasodilation. Abstract: The traditional renin-angiotensin system (RAS) is indispensable system in adjusting sodium homeostasis, body fluid volume, and controlling arterial blood pressure. The key elements are renin splitting inactive angiotensinogen to yield angiotensin (Ang-I). Ang-1 is then changed by angiotensin-1 converting enzyme (ACE) into angiotensin II (Ang-II). Using PubMed, Google Scholar, and other means, we searched the peer-reviewed literature from 1990 to 2013 for articles on newly discovered findings related to the RAS, especially focusing on how the system influences the central nervous system (CNS). The classical RAS is now considered to be only part of the picture; the discovery of additional RAS pathways in the brain and elsewhere has yielded a vastly improved understanding of how the RAS influences the CNS. Newly discovered effects of the RAS on brain tissue include neuroprotection, cognition, and cerebral vasodilation. A number of brain biochemical pathways are influenced by the brain RAS. Within various pathways, there are potential opportunities for classical pharmacologic interventions as well as the possibility of controlling gene expression.